Peristeen anal irrigation as a substitute for the MACE procedure in children who are in need of reconstructive bladder surgery - Alenezi, Husain; Alhazmi, Hamdan; Trbay, Mahmoud; Khattab, Amna; Neel, Khalid Fouda (Canadian Urological Association Journal, 2014)
Introduction: We evaluate the efficacy of the Peristeen (Coloplast A/S, Kokkedal, Denmark) transanal irrigation (TAI) system, as a stool cleansing mechanism, to gain stool continence in children who need reconstructive bladder surgery and have fecal incontinence. Methods: We prospectively evaluated children with neuropathic bladder and bowel dysfunction who were intended for reconstructive bladder surgery and the Malone antegrade continence enema (MACE) procedure. All patients were started on the Peristeen TAI system at least 3 months before surgery to assess their response. Each patient’s bowel function, frequency of using the system, satisfaction (and that of their parents) and diaper independency were evaluated before and after reconstructive surgery. Results: We included 18 patients (11 female, 7 male) who were evaluated from April 2006 to the present. The mean age of the group was 7.6 years (range: 4-15). Fifteen patients (83.3%) showed complete dryness from stools. Of the 15 patients, 8 (53.3%) were able to be diaper-free, while 6 continued wearing diapers due to fear of soiling and 1 due to urinary incontinence. The patients underwent reconstructive bladder surgery and continued to use the Peristeen TAI system with the same results postoperatively. The main limitation of this study is the small number of patients included, although this is a very specific patient group. Conclusion: Our initial results suggest that the Peristeen TAI system is a successful conservative substitute for the MACE procedure in children who require reconstructive bladder surgery.